2019
DOI: 10.1055/a-1018-9564
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function in Patients with Subclinical Hypothyroidism: A Meta-Analysis

Abstract: The purpose of this meta-analysis was to determine whether patients with subclinical hypothyroidism (SCH) have impaired endothelial function, which is assessed by carotid intima-media thickness (C-IMT) and flow-mediated dilatation (FMD) of brachial artery. PubMed, Embase and Cochrane Library databases and the key studies references were searched in our study, prior to July 2017 for all langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 61 publications
(44 reference statements)
0
19
0
3
Order By: Relevance
“…Multiple studies in patients with subclinical hypothyroidism have shown the association with cardiovascular abnormalities, like impaired endothelial function, increased IMT, left ventricular dysfunction, heart failure, coronary artery disease, and cardiovascular death. Many of these studies proved the substantial contribution of dyslipidemia, hypertension, obesity, insulin resistance, and metabolic syndrome in these complications (7,32). The recently published meta-analyses on early atherosclerosis in SH patients showed that severity of thyroid hormones disturbance is closely associated with the degree of arteries' function and structure, but other factors, like additional diseases, could not be ruled out (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies in patients with subclinical hypothyroidism have shown the association with cardiovascular abnormalities, like impaired endothelial function, increased IMT, left ventricular dysfunction, heart failure, coronary artery disease, and cardiovascular death. Many of these studies proved the substantial contribution of dyslipidemia, hypertension, obesity, insulin resistance, and metabolic syndrome in these complications (7,32). The recently published meta-analyses on early atherosclerosis in SH patients showed that severity of thyroid hormones disturbance is closely associated with the degree of arteries' function and structure, but other factors, like additional diseases, could not be ruled out (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies proved the substantial contribution of dyslipidemia, hypertension, obesity, insulin resistance, and metabolic syndrome in these complications (7,32). The recently published meta-analyses on early atherosclerosis in SH patients showed that severity of thyroid hormones disturbance is closely associated with the degree of arteries' function and structure, but other factors, like additional diseases, could not be ruled out (32,33). The scientific research on the relevance of low-normal thyroid function on components of the metabolic syndrome (MS) shows that the state is significantly associated with all components of MS (34).…”
Section: Discussionmentioning
confidence: 99%
“…TH supplementation improves blood lipid profile in overt hypothyroid patients and arterial stiffness in SHypo patients [16]. Compared to euthyroid individuals, patients with SHypo develop hypertension, dyslipidemia, endothelial dysfunction, and myocardial fibrosis more frequently and are more prone to CAD events and CAD deaths [20,22,23].…”
Section: 23mentioning
confidence: 99%
“…Thyroid hormones may cause interference with the renal blood flow due to their association with cardiovascular alterations [17,18]. Hypothyroidism is often associated with severe alterations in the blood lipid profile, greater risk of atherosclerosis and endothelial damage [19,20,21]. The interplay between thyroidism and nephropathy is very common and wellrecognized [22, 23, 24].…”
Section: Discussionmentioning
confidence: 99%